Immediate Effect of LED Cluster on Masticatory Muscles in Children and Adolescents Diagnosed With Down Syndrome: A Pilot Study: Immediate effect of LED clusters on masticatory muscle - Zaratin Beltramin, Rafael; Mendes Rocha, Monise; Politti, Fabiano; Melo Deana, Alessandro; Agnelli Mesquita-Ferrari, Raquel; Porta Santos Fernandes, Kristianne; Paula Taboada Sobral, Ana; Kalil Bussadori, Sandra (Journal of Lasers in Medical Sciences, 2025)
Introduction: Individuals diagnosed with Down syndrome (DS) often exhibit muscle hypotonia, particularly affecting the facial and oropharyngeal muscles involved in the mastication cycle. This condition impairs essential functions such as swallowing, speech, and chewing. Moreover, lingual hypotonia in individuals with DS can lead to problems such as snoring, obstructive sleep apnea, and bruxism. The aim of the present study was to investigate the activity of the masticatory muscles (masseter and temporalis) in individuals with DS and bruxism through electromyographic analyses before and after the application of red light-emitting diode (LED) clusters. Methods: Ten participants, four to 17 years of age, with diagnoses of DS and bruxism were assessed at the Integrated Health Clinic of Nove de Julho University. The masticatory muscles of the participants were submitted to electromyography (EMG) before and after the application of red LED clusters. Each cluster contained six LEDs with a wavelength of 660 nm, an optical point of 5 ± 2 mm, a dose of 2.675 J/cm², and an optical output of 2-5 mW. Results: The electromyographic analysis revealed changes in muscle activity after the application of the LED cluster. A reduction in asymmetry was found between the right and left masseter and temporalis muscles, and greater neuromuscular stability was found in the right masseter muscle. Although not statistically significant, these changes suggest immediate neuromodulatory effects. Conclusion: Although no statistically significant differences were found, the electromyographic patterns suggested improved muscle symmetry and neuromuscular stability following a single application of the LED cluster. These findings indicate the need for further investigation into the short-term effects of photobiomodulation in this population.